Land Procurement by Land Bank as a Form of Agrarian Reform Based on Law Number 11 Year 2021 Concerning Work Creation - Andriawan, Wisnu; Winantyo, Astari Cahyaningtyas; Juwono, Inigo Putera Bagus; Rahmani, Putri Mindya (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the implementation and position of the Land Bank in the legal system in Indonesia and the relationship between Law Number 11 of 2021 concerning Job Creation. The amount of land in Indonesia is not commensurate with the increasing need for physical development. This is closely related to the vulnerability of conflicts that occur in the community. The presence of a Land Bank is expected to minimize the occurrence of conflicts because the existence of a Land Bank is intended to address land needs. However, in an effort to realize this, the position of the Land Bank Institution has several things that may cause obstacles in the implementation of agrarian reform itself. This research uses a statutory approach (statue approach) and a conceptual approach. With the conclusion, that the construction of regulatory law related to the Land Bank creates legal certainty and benefits. Land Banks should also be in line with the realization of agrarian reform.